Building Student Talents and Future Leaders through Psychological Climate - Yogi Yunefri; Zamzami Zamzami; Heleni Filtri; Sri Wahyuni; Iskandar Agung; Opik Abdurrahman Taufik (AL-ISHLAH: Jurnal Pendidikan, 2023)
Realizing a generation of talented future leaders requires special programs from educational institutions which of course, are massively and consistently accepted by individuals every day. Talent development must be realized through the development of a positive psychological climate, supporting student leadership potential. Talented leaders will create positive perceptions for the members of the organization or institution they lead. The perception that the individual has is psychological climate. This research aims to develop a model for higher education policies to develop talents and future leaders through a valid, effective, practical Psychological Climate. The methodology used is Research and Development, development methods and procedures apply an analytical, conceptual model that describes the product components to be developed. The effectiveness and practicality test was carried out by applying the product to 100 students from 10 faculties. The data analysis technique used is descriptive analysis and different tests using SPSS version 20.00. The results of this study are that the preparation of basic leadership training manuals and the acquisition of talents and student leadership based on psychological climate has increased between before and after being given basic leadership training based on psychological climate.